A comparative analysis of results of the group expert assessment of metrological assurance of measurements - Velychko, Oleh; Gordiyenko, Tetyana; Kolomiets, Leonid (Eastern-European Journal of Enterprise Technologies, 2017)
Modern methods and means for conducting a group expert assessment are researched. The improved method of group expert assessment, which takes into account the competence of the experts involved on the basis of previously established criteria is proposed. This is important, since for the purpose of obtaining reliable estimates by a group expert assessment, it is first of all necessary to correctly approach the selection of both the method and the experts involved in the study. The improved software tools on the basis of the developed method are proposed. They are based on the integration of the element of competence assessment of the experts involved into the software tools, has no restrictions on the number of experts and the number of questions (factors) that need to be analyzed, and also allows, if necessary, adjusting the applied evaluation criteria. This contributes to the improvement of the accuracy and reliability of the results of group expert assessment, as well as the elimination of errors in calculating the results. An estimation of the state of metrological assurance for different types of measurements (by the improved method) is carried out. The analysis of the state of metrological assurance for all types of measurements has shown that 34 % of the sub-questions are prioritized for further detailed analysis, and 66 % do not have a priority or any significance at all for their further analysis. An examination of the consistency of the expert estimates obtained using the Kendall’s coefficient of concordance and the Pearson’s chi-squared test is carried out